Implementasi Pembelajaran Berbasis Bermain Imajinasi menggunakan Buku Cerita untuk Mengembangkan Kesadaran Lingkungan Anak - Indrie Larasati Hidayat; Ade Dwi Utami; Indah Febriyyani (PERDULI: Jurnal Pengabdian kepada Masyarakat, 2024)
The outreach program on imaginative play education has been conducted since 2022 and followed up in the Thousand Islands with the aim of improving the quality of early childhood educators (PAUD). The Thousand Islands, as an area of DKI Jakarta with limited access, was chosen as the location for the outreach to equalize the quality of educators. The approach to imaginative play using the STEM method was introduced through outreach, group discussions, and practice sessions. This outreach involved 15 teachers from the islands with the largest populations in the Thousand Islands, namely Pulau Panggang and Pulau Pramuka. Based on the activities, it was evident that the development of learning that includes STEM content is still not fully understood and implemented. The implementation of learning based on imaginative play also remains unfamiliar to teachers. The involvement of teachers in imaginative play activities is still a novel concept, as teachers tend to have the understanding that they must dominate play activities.